MODEL KOMUNIKASI AL-QUR’AN DALAM KISAH NABI MUSA DAN FIR’AUN: (KAJIAN QAS}AS} AL-QUR’A>N) - Mufida Ulfa (Indonesian Journal of Islamic Communication, 2021)
Abstract: One of the methods used by the Qur'an to convey its teachings is to present stories known as Qas}as} al-Qur'a>n. With a story, it is hoped that the children of this nation can take a lesson/wisdom from the experiences of the characters in the story, if it’s good then it should be used as an example but if it’s bad then it should be avoided. One of the stories featured in the Qur'an is about the da'wah of the Prophet Musa. to the king of Pharaoh. From here, the author wants to know how the model and effectiveness of communication used by Prophet Musa as. against Pharaoh. This research is library research, where the object of the study is the verses of the Qur'an. While the method used is the maud}u’i or thematic method and for the analysis used is Content Analysis. The result of this research is the communication model that the Prophet Musa uses is with Qaulan Layyina, where this communication model is one of the communication models in the Qur'an. Communication models in the Qur'an include: Qaulan bali>gha>, qaulan maisu>ra>, qaulan layyina>, qaulan kari>ma>, qaulan ma'ru>fa>, and qaulan sadi>da>. Meanwhile, if studied from communication theory, then K. Berlo's model is more suitable to describe the communication model of Prophet Musa. and this Pharaoh. Meanwhile, the effectiveness of this communication model is based on the story of the Prophet Musa as. This is quite effective by looking at many of the Bani Isra>i>l who followed the invitation of Prophet Musa.